2012
DOI: 10.1097/wnr.0b013e328359566e
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MSP58 suppresses cell proliferation in neuroblastoma cell lines

Abstract: MSP58, a novel oncogene, shows transforming activity in mouse embryonic fibroblasts. However, the oncogenic role of MSP58 in tumor cells has not been fully characterized. To extend understanding of how this protein operates in tumorigenesis, we aimed to identify the effect of MSP58 on neuroblastoma cell proliferation. Here, we found that MSP58 was highly expressed in neuroblastoma tumor samples and cell lines. We found that the majority of MSP58 protein can be detected in the nucleus as reported in other cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…MSP58si markedly reduced the proliferation and promoted the apoptosis of HepG2 and Huh7 cells and the Kaplan-Meier survival analysis in patients with HCC demonstrated that the survival time of the patients with low MSP58 expression was significantly longer than those with high expression during the 5-year follow-up period [6]. It was found that MSP58 was highly expressed in neuroblastoma tumor samples and cell lines and MSP58 targeted shRNA lentivirus attenuated neuroblastoma cell proliferation [25]. Our previous study also showed that MSP58 play an important role in glioma cell lines biological progression [7] and we further demonstrated that MSP58 expression correlates with the WHO grade and overall survival of patients with glioma [8].…”
Section: Discussionmentioning
confidence: 97%
“…MSP58si markedly reduced the proliferation and promoted the apoptosis of HepG2 and Huh7 cells and the Kaplan-Meier survival analysis in patients with HCC demonstrated that the survival time of the patients with low MSP58 expression was significantly longer than those with high expression during the 5-year follow-up period [6]. It was found that MSP58 was highly expressed in neuroblastoma tumor samples and cell lines and MSP58 targeted shRNA lentivirus attenuated neuroblastoma cell proliferation [25]. Our previous study also showed that MSP58 play an important role in glioma cell lines biological progression [7] and we further demonstrated that MSP58 expression correlates with the WHO grade and overall survival of patients with glioma [8].…”
Section: Discussionmentioning
confidence: 97%
“…In mouse, Mcrs1 also is expressed in the branchial arches and the otocyst (Gray et al, 2004). In mammalian cancer cells Mcrs1 has been implicated in proliferation (Shi et al, 2009; Wu et al, 2012; Zhong et al, 2013), and shown to function as a transcriptional repressor (Hsu et al, 2014). Mcrs1 also associates with the Fragile X mental retardation protein (FMRP) and may be involved in escorting silent ribonucleoparticles from the cell body of neurons to their distant synapses for translation (Davidovic et al, 2006).…”
Section: Six1 Co-factorsmentioning
confidence: 99%
“…In addition to participating in mitotic spindle assembly and mTOR signaling, MCRS1 is an oncogene [ 14 , 15 ]. MCSR1 has been found to be overexpressed in neuroblastoma, lung cancer, gastric cancer, liver cancer, colorectal cancer, and kidney cancer, and is associated with increased tumor growth, invasion and metastasis [ 15 , 16 , 17 , 18 , 19 , 20 ]. In 2019, using two gastric cancer cell lines (BGC-823 and SGC-7901), Wang et al found that suppressing MCSR1 expression can inhibit tumor activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%